(untitled) - Davis, Kingsley (New York, 1949)
This impressive, forward thinking research based survey focuses on five key concepts to explain sociological principles: function, structure, action, culture, and power. These concepts enable the text to present structural sociology and culture more fully than in any other book. The seventh edition continues to combine a balanced presentation with lively, student- oriented examples. This edition has been significantly revised, it features increased coverage of the founders of sociology, a greater emphasis on the structure of social interaction, and it introduces exciting and new "Sociology and Public Debates" and "Research Methods" boxes that students will find both evocative and engaging.
Keywords: Sociology,Xã hội học